2020
DOI: 10.1101/2020.04.23.058263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sphingosine-1-phosphate receptors 1 and 3 regulate the expression of scavenger receptor B1 in human aortic endothelial cells

Abstract: words)Several vasoprotective functions of high-density lipoproteins (HDL) on the endothelium have been shown to depend on the presence of sphingosine-1-phosphate (S1P) receptors (S1PRs) as well as scavenger receptor class B type 1 (SR-B1). Interference with the presence of S1P or the activity of S1PR1 or S1PR3 mimics many effects seen by the interference with SR-B1. This raises the question on interactions between S1P receptors and SR-B1. We investigated the influence of S1PRs on SR-B1 expression in human aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In support of interaction, it has been suggested that SR-BI tethers HDL on the cell surface and thereby increases the likelihood of S1P/S1PR interaction [ 77 , 78 ]. Moreover, our lab showed that siRNA mediated knockdowns of S1PR1 or S1PR3 reduce the expression of SR-BI [ 79 ].…”
Section: Promotion Of Endothelial Function and Integrity By Hdlmentioning
confidence: 99%
“…In support of interaction, it has been suggested that SR-BI tethers HDL on the cell surface and thereby increases the likelihood of S1P/S1PR interaction [ 77 , 78 ]. Moreover, our lab showed that siRNA mediated knockdowns of S1PR1 or S1PR3 reduce the expression of SR-BI [ 79 ].…”
Section: Promotion Of Endothelial Function and Integrity By Hdlmentioning
confidence: 99%
“…Moreover, we previously reported decreased SR-BI mRNA and protein expression of SR-BI in HAECs after knockdown of S1P 1 . 41…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we previously reported decreased SR-BI mRNA and protein expression of SR-BI in HAECs after knockdown of S1P 1 . 41 The in vitro findings regarding S1P 1 activation and its role in the transendothelial transport were principally recapitulated under in vivo conditions. In mice, both treatment with the S1P 1 agonist and the endothelium-specific overexpression of S1P 1 led to increased transport of fluorescent HDL from the bloodstream into the peritoneal cavity.…”
Section: Figure 5 Effects Of S1p 1 (Sphingosine-1-phosphate Receptor ...mentioning
confidence: 94%
“…SR-BI is also regulated by S1P on both the transcriptional and the posttranslational level [189]. Interestingly, both the S1P1 receptor and the S1P3 receptor regulate the transport of HDL and LDL oppositely.…”
Section: Regulationmentioning
confidence: 99%